Recent trends and scenario of antibiotic use in veterinary practices for livestock production in Bangladesh: a review (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
Antibiotics are used for the treatment and control of diseases as well as a growth promoter in livestock production in Bangladesh. The frequent use of these antibiotics in veterinary practices may lead to residue and creates some potential problems not only in livestock but also in public health issues. The presence of residues of antibiotics in animal-derived foodstuffs may induce carcinogenic and mutagenic effects and leads to the condition of an allergic reaction, and the development of antibiotic resistance in human gut bacteria. Although misuse of antibiotics in human medicine is the principal cause of the problems, some antibiotic-resistant bacteria originating in animals may also be the contributory factors to the resistance. However, some of the antibiotic resistance problems can be attributed to the transfer of resistant bacteria from animals to humans and resistance genes from animal pathogens and commensal bacteria to human pathogens. Even though the antibiotics and their residues in feed and food products of animal origin cause serious public health problems but little is known by society due to the lack of proper information. So, this is important to review the uses of antibiotics in food animals and insight their public health significance in Bangladesh. However, the safety levels of animal feeds and food of animal origin must be strictly observed and the antibiotics should be used in accordance with the labeled directions public awareness should be developed about the indiscriminate use of antibiotics in animals and their hazardous residual impacts on the human body. Therefore, the present review focuses on the aspects of antibiotic use in the livestock production of Bangladesh.Asian Australas. J. Biosci. Biotechnol. 2022, 7 (3), 90-106